2022
DOI: 10.3390/ijms23020626
|View full text |Cite
|
Sign up to set email alerts
|

Telomere and Telomerase-Associated Proteins in Endometrial Carcinogenesis and Cancer-Associated Survival

Abstract: Risk of relapse of endometrial cancer (EC) after surgical treatment is 13% and recurrent disease carries a poor prognosis. Research into prognostic indicators is essential to improve EC management and outcome. “Immortality” of most cancer cells is dependent on telomerase, but the role of associated proteins in the endometrium is poorly understood. The Cancer Genome Atlas data highlighted telomere/telomerase associated genes (TTAGs) with prognostic relevance in the endometrium, and a recent in silico study iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…NHP2, otherwise known as H/ACA ribonucleoprotein complex subunit, is an oncogene, like BRF2, and belongs to the H/ACA small nucleolar ribonucleoprotein (snoRNP) gene family and plays a crucial role in ribosome formation 36 and formation of the telomerase complex 37 . This latter function accounts for the gene's oncogenicity with increased expression having been observed in numerous cancers, such as endometrial cancer, 38 colorectal cancer, 39,40 and squamous cell lung cancer 41 . Most pertinent to this report, higher expression of NHP2, as well as other H/ACA snoRNP family genes, has also been correlated with poorer prognoses for HCC patients 42 .…”
Section: Discussionmentioning
confidence: 99%
“…NHP2, otherwise known as H/ACA ribonucleoprotein complex subunit, is an oncogene, like BRF2, and belongs to the H/ACA small nucleolar ribonucleoprotein (snoRNP) gene family and plays a crucial role in ribosome formation 36 and formation of the telomerase complex 37 . This latter function accounts for the gene's oncogenicity with increased expression having been observed in numerous cancers, such as endometrial cancer, 38 colorectal cancer, 39,40 and squamous cell lung cancer 41 . Most pertinent to this report, higher expression of NHP2, as well as other H/ACA snoRNP family genes, has also been correlated with poorer prognoses for HCC patients 42 .…”
Section: Discussionmentioning
confidence: 99%
“…mRNA levels of NHP2 and NOP10 indeed specifically distinguished non‐responders from responders to the Vistusertib + Anastrozole combination. Interestingly, it has been shown that NHP2 expression level was associated with prognosis in endometrial cancer [ 22 ]. Moreover, we also observed in a large dataset that high level of NHP2 was associated with poor outcome, in consistence with the fact that high NHP2 levels predict the lack of response to the Vistusertib + Anastrozole combination.…”
Section: Discussionmentioning
confidence: 99%
“…However, the difference in NOP56 expression between endometrial cancer and healthy endometrial epithelium was not statistically significant. Using statistical methods, NOP56 was found to be significantly and positively correlated with telomere-associated protein TERF2 ( 70 ). In the whole blood mRNA gene expression of metastatic renal cell carcinoma, the increase of NOP56 was statistically significant ( 71 ).…”
Section: The Expression Of Nop56 In Cancermentioning
confidence: 99%